Unique molecular surface features of in vivo tolerized T cells - Maier, Curtis C. (The National Academy of Sciences, 1998)
Differential expression of surface markers can frequently be used to distinguish functional subsets of T cells, yet a surface phenotype unique to T cells induced into an anergic state has not been described. Here, we report that CD4 T cells rendered anergic in vivo by superantigen can be identified by loss of the 6C10 T cell marker. Inoculation of Vβ8.1 T cell antigen receptor (TCR) transgenic mice with a Vβ8.1-reactive minor lymphocyte-stimulating superantigen (Mls-1(a)) induces tolerance to Mls-1(a) by clonal anergy. CD4 lymph node T cells from Mls-1(a) inoculated transgenic mice enriched for the 6C10(−) phenotype neither proliferate nor produce interleukin-2 upon TCR engagement, whereas 6C10(+) CD4 T cells retain responsiveness. Analysis of T cell memory markers demonstrate that 6C10(−) T cells remain 3G11(hi) but express heterogeneous levels of CD45RB, CD62L, CD44, and the CD69 early activation marker, suggesting that T cells at various degrees of activation can be functionally anergic. These studies demonstrate that anergic T cells can be purified based on 6C10 expression permitting examination of issues concerning biochemical and biological features specific to T cell anergy.